Single layer suturing in intracapsular myomectomy of intramural myomas is sufficient for a normal wound healing. (May 2020) - Prapas, Yannis; Zikopoulos, Athanasios; Petousis, Stamatios; Xiromeritis, Panayotis; Tinelli, Andrea; Ravanos, Konstantinos; Margioula-Siarkou, Chrysoula; Chalkia-Prapa, Eleni-Markella; Prapas, Nikos
Abstract: Study objective: To evaluate surgical outcomes of intracapsular single-layer myomectomy in terms of efficacy and safety as well as examine potential alterations based on kind of surgical approach. Methods: A prospective observational study was performed between January 2010 and December 2018. Women in reproductive age, affected by intramural or subserous myomas (FIGO type 3–6) of 4–14 cm diameter were enrolled. Primary outcomes included initial and final uterine incision length, time to wound healing and uterine rupture in subsequent pregnancies. Furthermore, a sub-analysis was also performed regarding surgical approach, namely laparoscopical or laparoscopically-assisted myomectomy, in order to confirm whether overall observations are similar for both potential surgical approaches. Results: There were finally 273 patients included in the present study. Overall mean uterine incision was initially 3.1 cm and was shortened to 2.2 cm at the end of operation, indicating a reduction of 29.1 %. Mean estimated blood loss was 154.2 mL and mean operative time was 82.1 min. No severe intraoperative and postoperative complications were presented. 121 of the studied women had pregnancy 3–36 months after myomectomy, without reporting any uterine rupture. When comparing LIM vs. LAIM, all outcomes were also favorable in the total of patients. Conclusion: Intracapsular myomectomy either by LIM or LAIM is a safe and attractive alternative to abdominal myomectomy in setting of premenopausal patients with myomas up to 14 cm. A single-layer continuous suturing in intracapsular myomectomies is enough for a successful wound healing.